O conhecimento na comunicação artística: o papel do corpo na exposição Sala de Jejum, de Milena Travassos - Dantas, Raquel Gonçalves (2011)
It is not a novelty that the body is a target to spotlights of researchers such within academy as in art sphere. For the study of this topic, it will be necessary to resort to the construction process and to the transformations that this human interface called body passed through the fifties, mainly in the artistic universe and in the reconstitution of the subject facing new paradigms. A special attention will be given to legitimating tacit knowledge, developed by Michael Pollanyi. Artistic experience provides to the man a way of knowing proper from the sensitive order. Human cognition is activated through mechanisms which escape from usual. This, without a question, alters cultural processes, as well as new possibilities of cognitive connections in human body. The legitimacy of other ways of knowledge through body sensitivity brings a new perspective to communication understanding. A new concept emerges in the beginning of this century: the Bodymedia Theory of Katz & Greiner. From this point, I question the ways of communication which happen within artistic experiences and what they have provoked in human body induced by many factors which are rulers of the current cultural and psychosocial process, among them, the new technologies. How is human Unwelt dilated and activated by artistic experience, based or not in technology? More specifically: how is human cognition altered by the complex exercise of an artistic experience? Starting with this problem, I will use the work of Milena Travassos, Sala de Jejum, as case study to build a structure for my research based upon the following hypothesis: human cognition is developed by a co-evolutive process related to human environment and technology offers a way of extrasomatisation relying on the body senses which accelerates such process, dilating the Unwelt of our specie. It will be present in this work the philosophical discussion of Jorge Vieira on the General Systems Theory. Giorgio Agambem will be present with the profanation concept. Intertwining with the discussion on the communication field, Jesús Martín Barbero, Nestór Garcia Canclini, Marshall McLuhan, Boaventura Sousa Santos will appear, as well as Walter Benjamin, author base to the studies of the visual artist analyzed. To discuss cognitive processes and the emerging of a new cultural communication, Muniz Sodré, Edward Hutchins, Helena Katz, Mark Johnson, Richard Sennet, António Damásio, among others